Height is a risk factor for development of peripheral insensate neuropathy - J., Sujjay; Green, Siva Ranganathan; A., Mohamed Kasim (International Journal of Advances in Medicine, 2019)
Background: Peripheral insensate neuropathy is one of the most common and forms of peripheral neuropathy. It is a preeminent cause for disability, foot ulcers, deformity and amputations in individuals who are at risk. Methods: A study was conducted in Mahatma Gandhi Medical College & Research Institute, Pondicherry, India in the year 2017-18, which included examination of 760 people of more than 30 years of age by random sampling method who was attending the outpatient clinic. The Semmes Weinstein monofilament was adopted to ascertain the presence of peripheral insensate neuropathy. Results: In present study, the prevalence of peripheral insensate neuropathy was 3.2%. As the height increased, the prevalence of peripheral insensate neuropathy increased, regardless of other independent risk factors like diabetes, hypertension, etc. The risk of the peripheral insensate neuropathy increases at a height of >171.5cm in males and at a height of >164.5cm in females. Conclusions: The authors confirm that body height is a significant and independent risk factor for peripheral insensate neuropathy, regardless of co-morbidities. Height as a guide, helps the health care professionals in identifying the people who are at risk for peripheral insensate neuropathy.